Leveraging learning science to improve student outcomes in asynchronous online medical terminology education - Kimberley Scott; Julie Young; Jeff Barbee; Marcia Nahikian-Nelms (Medical Education Online)
Background Online instruction within higher education is a growing trend. Asynchronous online courses vary widely in design elements. Research is needed to evaluate the impact of course design on student outcomes. A large, asynchronous undergraduate medical terminology course was modified to increase authentic language use, student interaction, formative feedback, retrieval practice, and metacognition. The purposes of this study were to describe modified course design elements and evaluate the impact of modifications on student outcomes compared with a standard course implemented concurrently.Methods This prospective, quasi-experimental study included 494 students (modified course, n = 277; standard course, n = 217). Measures included student participation, performance, course satisfaction, self-efficacy (SE), and engagement.Results Participation in assignments was high (88–94%). Students in both courses experienced growth in SE for medical terminology use. Students in the modified course earned significantly higher course grades and reported higher satisfaction levels. No significant differences in SE or exam scores were found between courses. Marginal significance was found for increased behavioral engagement for students in the modified course.Conclusions Modifications based on language learning and learning science principles were feasible to implement within a large, asynchronous online medical terminology course. Modifications resulted in greater student satisfaction and improved course grades. Exam performance was not significantly different between the modified and standard courses. Future research should focus on modifications preparing students for summative assessments.